Gambaran umum depresi pasca stroke di Poliklinik Neurologi RSUP Sanglah tahun 2015 - Hilda Citrajaya; Anak Agung Sri Wahyuni (DiscoverSys Inc., 2020)
Background: Nowadays, stroke is one of the leading causes of death globally. Defects caused by a stroke such as weakness or paralysis of the body cause the patient can not undergo normal daily activities. Depression can be a factor that slows the process of recovery or rehabilitation of stroke patients and it is very important to be prevented before it gets worse.Aim: To assess the general characteristics of post-stroke depression in Neurology Outpatient Clinic of Sanglah Hospital.Methods: The design of this research is descriptive with cross sectional study design. The Beck Depression Inventory (BDI) questionnaire was used as an instrument of data collection in this study. The study was carried out in Sanglah Hospital Neurological Clinic on 2015. Â Results: From 49 respondents, majority were female (29 subjects or 77.6%) and 15 were male (22.4%). The results showed that the prevalence of depression reached 34.7%.conclusion: Higher prevalence of depression was found in the sample group with age 56-87 (41.7%), working as a farmer (50%), with recent or non-school primary education (60%), income less than 1 million per month (52.9%), unmarried (100%), undergoing medical rehabilitation (38.9%), first episode of stroke (40%), last episode of stroke more than 180 days (38.4%) and being hospitalized more than 10 days (39.1%).Â Â Latar belakang: Dewasa ini, stroke menjadi salah satu penyebab kematian terbanyak secara global. Kecacatan yang diakibatkan oleh stroke seperti kelemahan atau kelumpuhan bagian tubuh menyebabkan pasien tidak dapat menjalani aktivitas sehari-hari dengan normal. Depresi dapat menjadi faktor yang memperlambat proses pemulihan atau rehabilitasi pasien stroke dan hal ini sangat penting untuk dicegah sebelum menjadi lebih parah.Tujuan: Untuk meneliti gambaran umum depresi pasca stroke di Poliklinik Neurologi RSUP Sanglah.Metode: Penelitian ini bersifat deskriptif dengan rancangan penelitian potong lintang (cross sectional). Kuesioner Beck Depression Inventory (BDI) digunakan sebagai instrumen pengumpulan data dalam penelitian ini di Poliklinik Neurologi RSUP Sanglah pada periode Maret-Agustus 2015.Hasil: Dari 49 orang responden, didapatkan mayoritas berjenis kelamin perempuan (29 orang atau 77,6%) dan 15 orang berjenis kelamin laki-laki (22,4%). Hasil penelitian menunjukkan bahwa prevalensi depresi mencapai 34,7%.Kesimpulan: Prevalensi depresi lebih tinggi ditemukan pada kelompok sampel dengan usia 56-87 (41,7%), bekerja sebagai petani (50%), dengan pendidikan terakhir SD atau tidak sekolah (60%), pendapatan kurang dari 1 juta per bulan (52,9%), belum menikah (100%), menjalani rehabilitasi medik (38,9%), mengalami stroke pertama kali (40%), waktu serangan stroke terakhir >180 hari (38,4%) dan lama rawat inap >10 hari (39,1%).